2018
DOI: 10.2147/tcrm.s168531
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of PD-1 mRNA expression combined with breast ultrasound in breast cancer patients

Abstract: IntroductionThis study explored the value of measuring programmed death 1 (PD-1) in peripheral blood, combined with breast ultrasound using the Breast Imaging Reporting and Data System (BI-RADS) classification, for differentiation between benign and malignant breast tumors.Materials and methodsWe enrolled 113 patients with breast cancer and 66 patients with benign breast tumors who were admitted to Hangzhou First People’s Hospital from September 2014 to August 2017. The mRNA level of PD-1 was detected by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It has been revealed that high expression of PD-1 on peripheral blood T cell subsets is correlated with poor prognosis of metastatic gastric cancer [73]. Fang et al [74] reported that the peripheral blood PD-1 expression was significantly higher in breast cancer patients than benign breast tumors. PD-1 and PD-L1 expression have been shown to be associated with adverse clinicopathological features in clear cell renal carcinoma [75].…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that high expression of PD-1 on peripheral blood T cell subsets is correlated with poor prognosis of metastatic gastric cancer [73]. Fang et al [74] reported that the peripheral blood PD-1 expression was significantly higher in breast cancer patients than benign breast tumors. PD-1 and PD-L1 expression have been shown to be associated with adverse clinicopathological features in clear cell renal carcinoma [75].…”
Section: Discussionmentioning
confidence: 99%
“…Serum tests are ideal, as they are repeatable, low-cost, and non-invasive. Previous studies have reported that expression of programmed death 1 and the neutrophil-to-lymphocyte ratio in peripheral blood could be diagnostic and prognostic indicators, respectively, in breast cancer 13,14…”
Section: Introductionmentioning
confidence: 99%